Qur’anic perspective on the role of education in the context of globalization: the alliance of civilization - Kayadibi, Saim; Malik, Mohammad Manzoor (IIUM Press, 2011)
The paper discusses the significance of education that may play a major role in instilling peaceful and mutual-understanding in the entire humanity. The moral teachings of religions lead to their common purpose to build peace and to maintain tranquillity among the people. Religions, in general, refer to the common origin of humanity; for example, this originality is symbolized in the first created couple, Adam and Eve, and it, in principle, makes all humanity brothers and sisters. However, to make this “common origin” known to people and foster peace and harmony among them based on the teachings of religions, there appears a compelling and serious necessity of a proper dynamic of education and educating. The paper seeks to elaborate how this reality can be achieved through the novel and extraordinary cross-continental and intercultural communication tools, which have come along with the most striking material and ideal phenomena called globalization.However, globalization that we all are living as a reality has besides its many bright sides some dark aspects as well. Material interpretation of globalization has driven attention and focus of people to the material fact of globalization and it has thus helped ignoring the spiritual possibilities that are present in globalization but are unnoticed and unexplored. This article tries to conclude its investigation through analyzing the following points: the role of education in the globalized world and its basic principles from the Qur’anic point of view. How the full capacity of humans can be achieved in order to discover its eternal values for harmony and coexistence. How education can play a significant role in the globalized world in unifying and focusing on the common values rather than dissecting and separating. How globalization can be made the proper channel and medium of the positive education, which can help realizing a global alliance of civilizations and its requirements.